Interfacial assembly of zinc(II) phthalocyanines on graphene oxide (GO): stable "turn-off-on" nanoplatforms to detect G-quadruplexes (G4) - Monteiro, Ana R. (2022)
Hypothesis The aggregation of phthalocyanines (Pcs) enfeebles their suitability as G-quadruplex (G4) ligands over time. It is hypothesized that the interfacial assembly of Pcs on graphene oxide (GO) influences intermolecular interactions, thereby affecting their physicochemical properties and inducing stabilization of Pcs in solution. Hence, the stacking of Pcs on GO could be tuned to create nanosystems with the ability to detect G4 for longer periods through a slow release of Pcs. Experiments Four cationic structurally-related zinc(II) phthalocyanines (ZnPc) were non-covalently assembled on GO by ultrasonic exfoliation. A comprehensive characterization of ZnPcs@GO was carried out by spectroscopic techniques and electron microscopy to understand the organization of ZnPcs on GO. The fluorescence of ZnPcs@GO was studied in the presence of G4 (T2G5T)4 and duplex ds26 through spectrofluorimetric titrations and monitored along time. Findings GO induced a re-organization of the ZnPcs mostly to J-aggregates and quenched their original fluorescence up to 98 % (“turn-off”). In general, ZnPcs@GO recovered their fluorescence (“turn-on”) after the titrations and showed affinity to G4 (KD up to 1.92 μM). This is the first report that highlights the contribution of GO interfaces to assemble ZnPcs and allow their slow and controlled release to detect G4 over longer periods.